Radermachera ramiflora - Tsen, S.; Colin Ruzelion Maycock; Damit, A.; Khoo, E.; Maryani, A.; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Radermachera ramiflora is confined to the western side of Sabah. It is found in four protected areas such as Kinabalu Park and Crocker Range forest reserve. The estimated extent of occurrence (EOO) and area of occupancy (AOO) are 1,438.5 km2 and 36 km2, respectively. It is suspected that at least 30% of the species population has been lost due to land use change in 88 years (in about two generations) based on reduction analysis in GeoCAT. Hence, this species is assessed as Vulnerable. Radermachera ramiflora is endemic to Sabah, Malaysia. It is confined to the western side of the state.